Cold tolerance, water balance, energetics, gas exchange, and diapause in overwintering brown marmorated stink bugs. (January 2021) - Ciancio, John J.; Turnbull, Kurtis F.; Gariepy, Tara D.; Sinclair, Brent J.
Graphical abstract: Highlights: Halyomorpha halys are chill-susceptible and die when overwintered outside. Diapausing H. halys have lower supercooling points, but unchanged cold tolerance. Diapausing H. halys have lower water loss and metabolic rates. H. halys likely rely on sheltered microhabitats to survive winter in Ontario. Abstract: Halyomorpha halys (Hemiptera: Pentatomidae) is an emerging pest which established in Ontario, Canada, in 2012. Halyomporpha halys overwinters in anthropogenic structures as an adult. We investigated seasonal variation in the cold tolerance, water balance, and energetics of H. halys in southwestern Ontario. We also induced diapause in laboratory-reared animals with short daylength at permissive temperatures and compared cold tolerance, water balance, energetics, and metabolism and gas exchange between diapausing and non-diapausing individuals. Halyomorpha halys that overwintered outside in Ontario all died, but most of those that overwintered in sheltered habitats survived. We confirm that overwintering H. halys are chill-susceptible. Over winter, Ontario H. halys depressed their supercooling point to c. −15.4 °C, and 50% survived a 1 h exposure to −17.5 °C. They reduce water loss rates over winter, and do not appear to significantly consume lipid or carbohydrate reserves to a level that might cause starvation. Overall, it appears that H. halys is dependent on built structures and other buffered microhabitats to successfully overwinter in Ontario. Laboratory-reared diapausing H. halys have lower supercooling points than their non-diapausing counterparts, but LT50 is not enhanced by diapause induction. Diapausing H. halys survive desiccating conditions for 3–4 times longer than those not in diapause, through decreases in both respiratory and cuticular water loss. Diapausing H. halys do not appear to accumulate any more lipid or carbohydrate than those not in diapause, but do have lower metabolic rates, and are slightly more likely to exhibit discontinuous gas exchange.